Clean and Healthy Living Behavior in The Effort to Break the Chain of Transmission of The Covid 19 - Dwi Priyantini; Setiadi Setiadi; Dedi Irawandi (STIKes Patria Husada Blitar, 2023)
The implementation of disease prevention behavior is influenced by the level of health literacy, which consists of several aspects including information, knowledge, understanding, and decision making. Health information is an important source related to the COVID-19 pandemic, both up-to-date information, prevention of exposure, what to do during isolation, and how to communicate with COVID-19 task force officers. The purpose of this study was to determine the correlation between health literacy and a clean, healthy lifestyle among STIKes Hang Tuah Surabaya students to break the chain. The research design used analytic observation with a cross-sectional approach. Data collection was obtained by participants filling out a questionnaire. Data analysis used the Spearman Rho correlation test with a P-value of 0.05. The results of the study showed that most of the students' health literacy was in the adequate category, and the students' clean and healthy living behaviors were in the high category. The results of the health literacy analysis was related to clean and Healthy Living Behaviors to break the chain of transmission of the COVID-19 pandemic in STIKes Hang Tuah Surabaya students. The research implication is that adequate health literacy will improve students' abilities regarding clean and healthy behavior (PHBS) to break the chain of transmission of the COVID-19 pandemic in STIKes Hang Tuah Surabaya students